PERAN SERTA ORGANISASI REMAJA ISLAM DALAM PENANAMAN NILAI-NILAI PENDIDIKAN ISLAM BAGI REMAJA SINDUAGUNG SELOMERTO WONOSOBO - Rifqi Muntaqo; Septi Rahayu; Ahmad Zuhdi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2019)
Islam has important life values to apply to people's lives, various methods of application have been exemplified by Islamic figures. The methods used include; exemplary, habituation, advice and punishment. This research takes the object of research in the youth of IPNU-IPPNU Sinduagung, the Islamic youth organization was formed in 2000-2001, over time the IPNU-IPPNU experienced a decrease in interest and not running various activities, so it changed its name to FORMAT (Mosque youth forum). And in the end the Islamic youth organization right on April 1, 2013 again turned into IPNU-IPPNU Sinduagung Selomerto Wonosobo. This study uses a qualitative method. The results showed that the planting of Islamic education values for adolescents in Sinduagung Village facilitated by various IPNU-IPPNU activities went very well, including by instilling the values of faith in makesta activities, then planting the values of worship in the pilgrimage pilgrimage activities, the values of moral values taken from the simulut duror maulid activities and in various humanitarian fundraising activities are important ways to explore the social values of Sinduagung Selomerto Wonosobo adolescents, with the hope that more care for their environment will increase.